2022
DOI: 10.1177/10126902221088124
|View full text |Cite
|
Sign up to set email alerts
|

Female elite sports achievements in Iran. The Case of the First Olympic Medalist

Abstract: The present study aims to identify the societal implications of the first-ever Iranian female medalist in the Olympics to date. We explored the meanings given to Kimia Alizadeh's success within Iranian society. We collected data through an examination of online news agencies and social networking sites using Leximancer software, a computer-assisted program for qualitative content analysis. This analysis uncovered four main themes: ‘women's sports and the dynamics of local-global policy’, ‘hope and determinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Although parents are a major driver to join sports (Chan et al , 2012), strict parents can also discourage female athletes from continuing their professional athletics careers (Kay, 2006), thus not supporting their sporting careers and professional branding efforts. Previous research has identified society as an obstacle to female athletes and their branding, as certain Muslim societies do not appreciate female sport participation, resulting in these athletes being harassed (AbdulRazak et al , 2010) or not being promoted (Ziaee et al , 2023). The media is also to blame, as the under-representation of women’s sports compared to men’s sports (Grubic, 2022; Valenti et al , 2018) and the sexualisation of women often result in negative perceptions of athletes in society (Kim and Sagas, 2014) and the resultant consideration of social media as a branding alternative.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although parents are a major driver to join sports (Chan et al , 2012), strict parents can also discourage female athletes from continuing their professional athletics careers (Kay, 2006), thus not supporting their sporting careers and professional branding efforts. Previous research has identified society as an obstacle to female athletes and their branding, as certain Muslim societies do not appreciate female sport participation, resulting in these athletes being harassed (AbdulRazak et al , 2010) or not being promoted (Ziaee et al , 2023). The media is also to blame, as the under-representation of women’s sports compared to men’s sports (Grubic, 2022; Valenti et al , 2018) and the sexualisation of women often result in negative perceptions of athletes in society (Kim and Sagas, 2014) and the resultant consideration of social media as a branding alternative.…”
Section: Discussionmentioning
confidence: 99%
“…As women’s sports and female athletes may be perceived differently, female athletes experience different challenges from male athletes (Doyle et al , 2021), such as receiving less media coverage (Romney and Johnson, 2020). Islam encourages participation in sport as it contributes to healthy living but, as professional athletes, Muslim women experience brand-building challenges from both a cultural and a religious context (Ziaee et al , 2023). Thus, this study focuses on understanding the brand-building obstacles Muslim women face, answering the call of Hasaan et al (2016a) and Sadeghi et al (2018) to investigate this phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…Female athletes are only praised and applauded by society if they are successful in sports such as figure skating and gymnastics. As this sport is already associated with the image of youth, flexibility and femininity, it again appears as an indicator of gender discrimination in sport (Willis, 1995). In South American newspapers, women's sports account for 15% of coverage, compared to 3% to 7% in all sports magazines and 1% to 3% in women's tabloid media.…”
Section: Discussionmentioning
confidence: 99%
“…While some countries, such as Saudi Arabia, have made significant progress in promoting women's participation in sport, others lag far behind the modern world (Benstead, 2017). In one of these countries, Iran, women are still prohibited from participating in men's sports competitions (Ziaee et al, 2023). On the other hand, countries such as Qatar and the United Arab Emirates actively promote women's sports by investing heavily in sports infrastructure.…”
Section: Women and Sports In Islammentioning
confidence: 99%